Cardiac metastasis of uterine cervical squamous cell carcinoma: A case report and review of the literature - Takeda, Yoshihiro (J Cardiol Cases, 2014)
A 48-year-old woman was referred to the cardiology department due to a large mobile mass in the right ventricle. The patient had undergone radical hysterectomy and bilateral salpingo-oophorectomy for a uterine squamous cell carcinoma approximately 3.5 years before. In order to protect the patient from circulatory collapse, the intracardiac mass was resected surgically. A diagnosis of cardiac metastasis of the uterine cervical squamous cell carcinoma was confirmed histologically. Herein we discuss the possible therapeutic approach to and prognosis of this rare condition by reviewing 24 papers on intracardiac uterine cancer metastasis published in the past 10 years. <Learning objective: A woman who had undergone radical hysterectomy and bilateral salpingo-oophorectomy for a uterine squamous cell carcinoma 3.5 years before was referred to the cardiology department due to a large mass in the right ventricle. The diagnosis of cardiac metastasis of the uterine cervical squamous cell carcinoma was confirmed histologically. Although metastasis of cervical carcinoma to the cardiac cavity is rare, we should not overlook this possibility during the post-operative patient follow-up.>